Collateral regimes and missing job creation in the MENA region - Frank Betz; Farshad R. Ravasan (European Investment Bank (EIB), 2016)
The economies in the Middle East and North Africa have not been able to generate a sufficient number of jobs for a fast growing population. This paper uses data from the MENA Enterprise Survey to investigate the extent to which prevailing collateral practices affect the allocation of credit and firms' ability to expand and create jobs. Using matched bank-firm data to recover banks' collateral policies and exploiting data on the location of firms and bank branches, the paper aggregates the estimated collateral policies into branch-weighted indices that represent collateral practices at the local level. We find that less stringent collateral regimes are conducive to employment growth. Young firms in particular benefit from lower collateral ratios, while a greater willingness to accept movables benefits both young and old firms.
Keywords: 330